The Conditions and Guidelines for Student Club Administration in Nanning Normal University, People's Republic of China - Yuan, Lei; Kultanan, Phatchanee; Poldech, Sripen (วารสารศิลปะและวัฒนธรรมลุ่มแม่น้ำมูล, 2025)
There are multiple challenges within the student club at Nanning Normal University, including deficiencies in financial record-keeping, low member participation, and inadequate risk management for activities. These issues significantly impede the sustainable development of the student club. Therefore, this study aims to investigate the conditions and guidelines for student club administration in Nanning Normal University. The study sample consists of 377 student members from 23 student clubs at Nanning Normal University. Data collection tools include questionnaires and semi-structured interviews, which cover the current status and guidelines of student club administration at the university. The questionnaire includes 41 questions, utilizing a 5-point Likert scale, with the item correlation values ranging from 0.442 to 0.771 and a reliability of 0.975. Additionally, the semi-structured interviews were designed based on two questions from the three aspects with the lowest average scores in the questionnaire. Data analysis was conducted using frequency, percentage, mean, standard deviation, and content analysis methods. The research results found that: 1. The overall level of conditions and guidelines for student club administration at Nanning Normal University is relatively high. Financial management received the highest average score, followed by student club activity management. 2. Guidelines for student club administration in Nanning Normal University across three aspects. The development guidelines are as follows: 1) Financial Management, student clubs should establish a scientific financial planning system and strict financial management policies to ensure transparency and efficiency in fund usage. Data collection and regular financial disclosures should be conducted to enhance members' sense of involvement. 2) Human Resource Management, student clubs should improve member engagement satisfaction by implementing transparent selection processes, fair evaluation standards, and incentive mechanisms. Attention should also be given to members' mental health and academic balance. 3) Activity Management, student clubs should implement comprehensive risk assessments and contingency plans, establish feedback mechanisms, and optimize activity content to enhance activity quality and strengthen members' sense of belonging. The research findings will serve as guidelines for the effective management of student clubs.